Impulse Source in the Vicinity of a Convex Impedance Body: Minimization of the Field in the Shadow Region - Zvyagintsev, A.A.; Ivanov, A.I.; Katkov, D.V. (Радиофизика и радиоастрономия, 2002)
The work deals with the optimization problem of impulse source field minimization in the shadow region of a convex body with variable surface impedance. The optimal impedance is searched using uniform asymptotic methods and Ritz method for functional minimization. Numerical results are presented for the Gaussian impulse source. В настоящей работе представлен метод определения оптимального покрытия поверхностей (поверхностного импеданса), при котором достигается минимум поля точечного импульсного источника в точке наблюдения, расположенной в тени относительно этого источника. Метод основан на геометрической теории дифракции и равномерных асимптотических методах, а также на методе минимизации функционалов Ритца. У роботі представлено метод визначення оптимального покриття поверхонь (поверхневого імпедансу), при якому досягається мінімум поля імпульсного джерела у точці спостереження, яка розташована у тіні відносно цього джерела. Метод засновано на геометричній теорії дифракції та рівномірних асимптотичних методах, а також на методі мінімізації функціоналів Рітца.